IMPLEMENTASI AKUNTANSI PERTANGGUNGJAWABAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERSPSEKTIF SYARIAH - Diah Nurdiwaty; Sigit Wisnu Setya Bhirawa (Istithmar: Jurnal Studi Ekonomi Syariah, 2017)
This research is based on the researcher’s observation that there are still many companies in Indonesia that ignore the surrounding environment. In the Qur’an, it is explained that man was created as God’s representative on earth. The responsibility of human as earth successor is to maintain and care for the earth and whole things in it can be managed properly. The problems in this research are (1) The influence of Environmental Cost on the implementation of Environmental Accounting (2) The Influence of Return on Asset to the Implementation of Environmental Accounting (3) Influence of Corporate Types Against Environmental Accounting Implementation. In this research, using descriptive quantitative approach. The sample used is purposive sampling technique in 16 companies. While the data analyses using logistic regression, the independent variables are environmental cost (X1), ROA (X2) and company type (X3), while for the dependent variable is the implementation of environmental accounting. The conclusion of this study is that environmental costs a major consideration in the implementation of environmental accounting, environmental and interrelated accounting cost. Companies with high ROA do not apply environmental accounting. The types of companies that apply the most environmental accounting are manufacturing and service companies.